Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1116/1.590731
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy growth of boron-containing nitrides

Abstract: Layers of BN, BGaN and BAlN were grown by molecular beam epitaxy using ammonia on (0001) sapphire substrates. The crystal structure and material quality of these layers were assessed by reflection high energy electron diffraction, x-ray diffraction, Fourier transform infrared reflectance, and photoluminescence spectroscopy. These measurements reveal that while BN layers grow as polycrystalline films, BGaN and BAlN layers grow as single crystals with boron composition up to 2% and 6%, respectively. A monotonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 4 publications
(2 reference statements)
0
27
0
Order By: Relevance
“…[2][3][4][5][6][7] Recently, there have been many attempts to develop a reproducible technology for the growth of large area boron nitride layers by chemical vapor deposition, [19][20][21] metalorganic chemical vapor deposition 8,9,22 and molecular beam epitaxy (MBE). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Progress in MBE growth of boron nitride layers has been relatively slow, partly due to a lack of an efficient MBE source for boron, due to its very low vapor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Recently, there have been many attempts to develop a reproducible technology for the growth of large area boron nitride layers by chemical vapor deposition, [19][20][21] metalorganic chemical vapor deposition 8,9,22 and molecular beam epitaxy (MBE). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Progress in MBE growth of boron nitride layers has been relatively slow, partly due to a lack of an efficient MBE source for boron, due to its very low vapor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, the large error bars associated with the uncertainty of determining the frequency of the weak, broad E 2 peak on a raising background. It is known that the incorporation of higher boron concentrations is difficult [5]. Then, the samples with the highest boron concentration (3.0% and 3.6%) probably contain substantial composition inhomogeneities and a high density of defects, and this may explain the low E 2 frequencies observed in these samples.…”
Section: Resultsmentioning
confidence: 96%
“…However, the large lattice mismatch between GaN and BN results in considerable internal strain, making it difficult to grow BGaN with an appreciable boron concentration before phase separation occurs [3]. Successful growth of B x Ga 1-x N alloys is achieved only for very low boron contents, typically x Շ 3% [4][5][6]. Since the formation enthalpy for B x Ga 1-x N is similar in trend and magnitude to that of GaAs 1-x N x , it has been suggested that high-quality BGaN single crystals with 5% boron may be possible [2].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to grow single crystal layers of cubic boron nitride (cBN) using molecular beam epitaxy technique have been made [1]. The results showed mainly amorphous or hexagonal modifications of boron nitride [1,2]. Incorporation of low composition (~1×10 17 cm -3 ) of boron in GaN has been reported [3].…”
mentioning
confidence: 95%
“…Due to low solubility of boron in GaN and AlN and its phase separation [4,5] it has not been possible to grow single crystalline layers of BGaN and BAlN alloys for all alloy compositions. However, MBE growth of BGaN and BAlN with up to 6% boron was reported [2]. Apart from lattice-matching problems, one practical obstacle is the low vapor pressure of elemental boron.…”
mentioning
confidence: 99%